THE EMPLOY OF LITERACY OF LITERACY WORK STATION IN DEVELOPING STUDENTS’ READING SKILL - Sudirman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research aimed to describe the employof literacy work station able to enhance the students’ reading comprehension. This Classroom Action Research was conducted at the first-grade students of SMPN 2 Praya with 26 students consist of 14 boys and 12 girls. This Research focused on the students’ learning on reading comprehension. This research consists of one cycle; each cycle consists of planning, action, observation, and reflection. The data gathering used written test, observation sheet, and questionnaires and analyzed the data are using qualitative and quantitative approach. After one cycle were conducted it could be seen from the mean score of students’ pre test (61, 3) with the precentage was15% and the mean score of students’post-test (82,1) with the percentage was 88%. The result of the students’ achievement with passing scores in test 1 were 50% (poor) and test 2 were 88% (very good) indicating the target of 75 of the minimum criterion has been achieved. Based on the result of the study, it can be concluded that the employ of literacy work station can enhance the students reading comprehension at the first grade of SMPN 2 Praya in Academic Year 2022/2023